Penggunaan Majas Perbandingan Dalam Puisi Karya Siswa Kelas VIII Di SMP N 3 ColomaduTahun Ajaran 2015/2016 - Mujiyati, Sri, Drs. Andi Haris Prabawa, M.Hum (2016)
Poetry is one of the literary works using beautiful language, compressed, shortened, which means purpose in it is not expressed directly by the author and disclosure by Cadence. That's necessary to use a figure of speech in writing poetry, because the value of the element kepuitisan beauty of poetry comes from the bermajas. This study aims to describe the use of a comparison figure of speech in a poem by the eighth grade students of SMP N 3 Colomadu, describing the students' skills in using the comparative figure of speech in poetry writing. This research is descriptive qualitative. Data collection techniques used in this study is the technique see and record. Methods of data analysis in this study using a unified referential. Data analysis techniques in this study using basic techniques pilah decisive element (PUP). The results of this study indicate that investigators found five varieties used figure of speech comparing preformance of poems by eighth grade students at SMP N 3 Colomadu, a fifth of the figure of speech that figure of speech personification, metaphor figure of speech, figure of speech simile, allegory figure of speech, and a figure of speech antithesis. The ability of class VIII SMP N 3 Colomadu in using a figure of speech comparing the poems they've been pretty good but the amount of use is still very small, so that the teaching of Indonesian language and literature should be emphasized, especially in terms of usage figure of speech comparison in poetry that poetry students' work is more beautiful and attractive. Keywords : figure of speech, a comparison figure of speech, poetry.